Performances and Working Mechanisms of Inclined Retaining Structures for Deep Excavations - Gang Zheng; Yuping Wang; Peng Zhang; Xuesong Cheng; Wenlong Cheng; Yuebin Zhao; Xinhao Li (Advances in Civil Engineering)
Because of the limits of struts, braceless retaining structures (BRS) have become a preferred option in deep excavation engineering. A type of BRS, that is, inclined retaining system, has been successfully applied in several projects. However, its performance and working mechanism have not been systematically studied. A case study and finite element results in this study show that inclined piles (IP) are more effective than vertical piles (VP), while composite inclined retaining structures (CIRSs) are more effective than IP in terms of deflection and bending moment reduction. The deformation-control mechanism of IP mainly comes from the decrease in the active earth pressure. For CIRSs, the working mechanism is governed by several combined effects, that is, the rigid frame effect, inclined strut effect, earth berm effect, and gravity wall effect. For instance, in composite vertical and inward-inclined piles (VIIP), inclined piles function as struts for the vertical piles in this rigid frame system and frictional force between the soil and the inclined piles significantly influences its retaining performance; the soil between the vertical and inclined piles plays a role similar to an earth berm; additionally, the entire retaining system is similar to a gravity retaining wall, which has relatively high overturning stability.